The Failure Behaviour of Reinforced Concrete Panels Under Far-field and Near-field Blast Effects. (June 2018) - Syed, Z.I.; Raman, S.N.; Ngo, T.; Mendis, P.; Pham, T.
Abstract: The distribution and intensity of blast pressure from far-field and near-field blasts can produce remarkably different patterns of loading on a reinforced concrete (RC) panel and can cause the panel to experience different modes of failure. Behaviour of RC panels, designed without consideration for extreme loading was investigated to analyse their damage and failure modes under different blast scenarios. The damage and failure modes of RC panels tested in two different full scale open air blast trials are presented. One of the tests was conducted in far-field condition with 40 m standoff distance. The other test was conducted on panels in near-field condition with standoff distances up to 2 m. These tested RC panels were subsequently modelled and analysed using the non-linear finite element (FE) code, LS-DYNA. Developed finite element models were used to conduct further parametric study to investigate damage behaviour and failure modes of RC panels under different blast loading conditions. The effect of blast pressure distribution and intensity on the failure modes of different RC elements were studied and blast pressure distribution and shock density were found to influence the mode of failure of a RC element significantly. Based on parametric study results, specific values of incident angle and shock density of blast pressure were suggested which can be used to predict the transition between failure modes of RC panels from shear to flexure for far-field and near-field blasts.